2007
DOI: 10.1103/physrevb.76.113409
|View full text |Cite
|
Sign up to set email alerts
|

Direct monitoring of plasmon resonances in a tip-surface gap of varying width

Abstract: We have studied the dependence of tip-enhanced Raman (TER) spectra composed of discrete Raman lines and an intense Lorentzian-shaped background on varying interparticle distance. For increasing tip-sample separation, we observe a remarkable blueshift of the background maximum that is ascribed to an energy shift of the localized surface plasmon resonance. In addition, we report on a steep background and Raman band intensity decrease within 5–10 nm tip retraction that highlights the underlying near-field enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 37 publications
11
126
0
Order By: Relevance
“…The agreement with the model is excellent as shown in Figs 6,7,8,9, and 11(a). Our modeling of the electron-hole spectra contrasts with all previous attempts that do not consider the whole frequency range [5,21].…”
Section: B Spectral Response For Electronic Scatteringmentioning
confidence: 71%
See 2 more Smart Citations
“…The agreement with the model is excellent as shown in Figs 6,7,8,9, and 11(a). Our modeling of the electron-hole spectra contrasts with all previous attempts that do not consider the whole frequency range [5,21].…”
Section: B Spectral Response For Electronic Scatteringmentioning
confidence: 71%
“…The impressive enhancement, up to 10 8 , of the vibrational fingerprint of molecules located at specific sites ("hot spots") on the surface of metallic particles is responsible of a further huge development of Raman spectrometry [2]. The possibilities of acquiring vibrational information down to a single molecule [3,4] and controlling a single hot spot with high spatial resolution using tip-enhanced Raman spectroscopy (TERS) [5][6][7][8] have led to new insights on local mechanisms at the origin of SERS. From the beginning, these mechanisms have been commonly referred to as electromagnetic (EM) [9] when due to local electromagnetic inductive effects, or chemical (CM) [10] when due to resonant charge transfer effects, the first one giving the largest contribution to the enhancement factor [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in background signal intensity has been recently attributed to photons emitted from annihilated inelastically scattered localized surface plasmons. [54] The TER bands observed at 1576, 1073, 1023, 1000, and 690 cm −1 can be clearly assigned to PhS (for assignments see Table 2). The wavenumbers agree well with the vibrational spectra of PhS on Au surfaces and Ag thiophenolate salts.…”
Section: Proof Of Principle: Ters Of Phs On Au In Water Using Protectmentioning
confidence: 99%
“…The resonance condition of surface plasmon is also affected by the gap distance. Pettinger et al reported [43] the dependence of TERS composed of discrete Raman lines and the intense Lorentzian-shaped background by varying tip-substrate gap in STM setup. Remarkable blue shift of the background, which means the energy shift of the localized surface plasmon resonance, was observed.…”
Section: Gap Mode Enhancementmentioning
confidence: 99%